Abortion and the politics of motherhood - Luker, Kristin (Berkeley : University of California Press, 1984)
This study of the abortion controversy in the United States argues that moral positions on abortion are intimately tied to views on sexual behaviour, the care of children, family life, technology, and the importance of the individual.
Medicine and morality in the nineteenth century -- The century of silence -- Abortion reform: the professional's dilemma -- Women and the right to abortion -- The emergence of the right-to-life movement -- World views of the activists -- Motherhood and morality in America -- The future of the debate.
Bibliography: p. 291-309.
Includes index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
JSTOR
Keywords: Right to Life Movement; Umschulungswerkstätten für Siedler und Auswanderer; Abortion -- United States; Abortion -- Political aspects -- United States; Pro-life movement -- United States; Motherhood -- Moral and ethical aspects; Politics, Practical; Abortion; Attitude (Psychology); Fetus; Individuality; Women's rights; Abortion, Therapeutic; Civil rights; Contraception; Cultural pluralism; History; Labor (Obstetrics); Mothers; Physicians; Pregnancy; Pregnant women; Social values; Motherhood -- Moral and ethical aspects -- United States; Abortion -- Political aspects -- United States; Politics; Abortion, Induced; Attitude; Beginning of Human Life; Fetus; Individuality; Life; Personhood; Public Policy; Women's Rights; Abortion, Legal; Abortion, Illegal; Abortion, Therapeutic; Civil Rights; Contraception; Cultural Diversity; Embryo, Mammalian; Family Relations; History; Jurisprudence; Labor, Obstetric; Moral Obligations; Mothers; Physicians; Pregnancy; Pregnant People; Sexuality; Social Responsibility; Social Values; United States; Motherhood -- United States -- Moral and ethical aspects; Avortement -- États-Unis.; Avortement -- Aspect politique -- États-Unis.; Maternité -- Aspect moral -- États-Unis.; Mouvement pour le respect de la vie -- États-Unis.